Chemical Composition of Rosemary Essential Oil Extracted With Microwave Assisted and Hydrodistillation Techniques by Gas Chromatography-Mass Spectrometer - Reem Mohammad Ayad Alqarni (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Rosmarinus officinalis L.essential oil is of high economic value; it is widely used several industries. Variation in essential oils yield and chemical composition is affected by the geographical region and the extraction method. Therefore, there is a growing interest in developing more efficient extraction methods that maintain the activity of chemical components of the oil. Microwave-assisted hydrodistillation extraction is a promising technique for extraction of essential oils. Aim:The purpose of this study is to study the effect of hydrdistillation and microwave-assisted hydrodistillation extraction methods on the yield and chemical structure of Rosmarinus officinalis L. essential oil. Rosmarinus officinalis L. were collected from five different geographical regions is Kingdom of Saudi Arabia (KSA); Abha, Asir, Al-Baha, Taif-Al-Hada, and Taif-Al-Haweya. The obtained oils were analyzed qualitatively and quantitatively using Gas chromatography-Mass Spectrometer to identify the components of the oils obtained using each method. Results:Both method identified a total of 44 compounds, the major compounds were Eucalyptol (P-Cineol) (44.68-25.70%), α-Pinene (22.68-7.48%),Camphor (13.74-3.48%), Bornyl Acetate (13.57-1.09%), Borenol (10.39-5.54%), Camphen (7.32-3.26%).Results also indicated that the geographic location and the environment influenced in chemical composition of Rosmarinus officinalis L. essential oil. Conclusion:This study compared the chemical composition and yield of rosemary essential oils from five regions in the KSA using hydrodistillation and microwave extraction methods. Results showed variations in strains and extraction methods, with microwave extraction achieving similar yields but limitations in energy consumption, extraction time, and environmental impact. Further research is needed to optimize methods, consider soil and climate effects, and determine suitable harvest time and season.